KEWAJIBAN UNTUK MENJAGA KERAHASIAAN AKTA OLEH NOTARIS DAN KARYAWAN NOTARIS DALAM PERSPEKTIF HUKUM - Rahmida Erliyani; Muhammad Hadin Muhjad; Lia Audia Puspita (Universitas Islam Malang, 2021)
The purpose of this study is to find out and understand the Witnesses' Essence and Testimony in notary law. And to know and understand the legal consequences for former Notary employees who provide information to open the confidentiality of the deed. The usefulness of this research is as information material within the framework of the development of science and insights in legal disciplines, especially notary law. And as a contribution of thought in enriching the horizons for the parties concerned. According to the results of the study that the position of witnesses in notary law is to meet the formal requirements of a deed. The position of a witness is a unity in a notarial deed, witnesses who come from Notary employees in practice in the field are not always employees who type the deeds of the parties. It is not uncommon for employees who are witnesses to the signing and reading of the deed to know only at the time the incident took place. So the Notary employee in his position as a witness is not obliged to remember the contents of the deed. As long as he does not commit illegal acts in his duties as a Notary employee to type the deeds of the parties, his existence in a notarial deed does not conflict with the provisions of the Notary compulsory to keep the contents of the deed.And how the obligation to be awarded the deed by o notary and notary employee ?